The Sensations of the 1920s:: Martha Ostenso’s Wild Geese and Mazo de la Roche’s Jalna - Hammill, Faye (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Martha Ostenso's Wild Geese and Mazo de la Roche's Jalna were both prize-winning, wildly successful novels, in the United States as well as in Canada, but each received a rather different critical response in this country. Jalna's suggestive anti-Americanism and its explicit British loyalism was evidently to be preferred over Wild Geese's more ambiguously North American (as opposed to what was then considered distinctly Canadian) aesthetic. This is despite its easy fit into T.D. Maclulich's classification as a Canadian "Northern" fiction (a tradition which includes Frederick Philip Grove, Ernest Buckler, Sinclair Ross, and others). As well, the intense and often violent eroticism of Ostenso's novel was more difficult for critics of the 1920s to tolerate than was the coy sexiness of Jalna. Although little critical attention has been paid to either author in recent years, Ostenso's literary reputation appears to have surpassed de la Roche's.